2022
DOI: 10.1002/ps.6785
|View full text |Cite
|
Sign up to set email alerts
|

Emamectin benzoate as a potential molluscicide against white garden snail, Theba pisana in association with biochemical defects

Abstract: BACKGROUND The white garden snail, Theba pisana, is distributed worldwide and is a serious molluscan pest of different crops. Emamectin benzoate (EMB) ‘an avermectin derivative’ is a novel biorational agent and highly effective pesticide. This study focused on the lethal and in vivo sublethal toxic effect of EMB on the energy reserves (glycogen, lipids and proteins), total energy reserves and activities of glutathione S‐transferase (GST), γ‐glutamyl transferase (γ‐GT), lactate dehydrogenase (LDH), aspartate am… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 52 publications
0
0
0
Order By: Relevance
“…However, after 3 days of exposure, there was non-significant effect in total protein. Also, a significant increase in total protein was indicated in T. pisana snails treated with 20 and 60% of emamectin benzoate for 1, 3 and 7 days compared with untreated snails (Gad, 2022). Kandil et al (2009 and2014) found that the total proteins in Monacha obstructa and Eobania vermiculata were increased when snails exposed to abamectin as a baiting technique or contact poison up to 7 days.…”
Section: Discussionmentioning
confidence: 96%
“…However, after 3 days of exposure, there was non-significant effect in total protein. Also, a significant increase in total protein was indicated in T. pisana snails treated with 20 and 60% of emamectin benzoate for 1, 3 and 7 days compared with untreated snails (Gad, 2022). Kandil et al (2009 and2014) found that the total proteins in Monacha obstructa and Eobania vermiculata were increased when snails exposed to abamectin as a baiting technique or contact poison up to 7 days.…”
Section: Discussionmentioning
confidence: 96%
“…Snails can leave an unpleasant odor on plants as a result of their mucous secretions during their movements causing contamination of plants and preventing animals from eating (Sallam et al, 2009). The most efficient way of control for mollusks is still chemical molluscicides, although several risks for people, animals, and almost all terrestrial organisms (Gabr et al, 2006;Gad, 2022)). Snails are hermaphrodites that sperms mature before eggs and have a reciprocal exchange of sperms during mating (Routray and Dey, 2016).…”
Section: Introductionmentioning
confidence: 99%